Flux model development and synthesis optimization for an enhanced GO embedded nanocomposite membrane through FFD and RSM approach - Mohamad Syafiq, Abdul Wahab; Sunarti, Abd Rahman; Rozaimi, Abu Samah (Elsevier Ltd, 2020)
A two-level full factorial design was used to analyze several factors involved in PSF–GO–Pebax thin film nanocomposite membranes development. Permeate flux was chosen as a single response for four possible factors: Pebax selective layer concentration, amount of GO load to Pebax selective layer, Pebax–GO selective layer thickness, and amount of GO load to PSF substrate. The study is aimed at factors interaction and contribution towards the highest permeation flux via FFD and RSM approach. R2 obtained from the ANOVA is 0.9937 with Pebax concentration as the highest contributing factor. Pebax concentration–amount of GO load to PSF substrate is the only interaction contributing to the highest flux. A regression analysis concluded the study with model development and an optimized condition for the membrane design.